Polymyxin B Direct Hemoperfusion Using Regional Citrate–Calcium Anticoagulation: A Case Report. Issue 11 (1st December 2016) - Sidoti, Anna; Brogi, Etrusca; Morse, Joshua; Collareta, Michele; Vetrugno, Luigi; Giunta, Francesco; Forfori, Francesco
Abstract : Direct hemoperfusion with polymyxin B (PMX-DHP) is an extracorporeal treatment to add to conventional therapy during unresponsive endotoxic septic shock. So far, only heparin has been used as an anticoagulant during polymyxin B therapy. We present a case report of a postsurgical septic patient treated with 2 cycles of PMX-DHP using citrate anticoagulation. Monitoring of serum calcium, postcartridge calcium, and acid–base balance was performed. The treatments were accomplished without complications. To our knowledge, this is the first published report on the use of citrate anticoagulation during PMX-DHP. We conclude that citrate anticoagulation is feasible during hemoperfusion therapy in patients with increased hemorrhagic risk.